The influence and effects of digital revolution on Africa’s higher education systems - Lumadi, R. I. (South African Journal of Higher Education, 2024)
This article explores the challenges posed by the digital revolution and its influence on the education system. Enthusiasm among digital natives for departing from traditional teaching methods in favour of digital tools to enhance higher education learning is evident. Employing document analysis, this research extracts valuable insights. The selection of published materials pertinent to migration is achieved through purposive and convenience sampling. The Technology Acceptance Model emerged as the suitable framework, highlighting that user perception of technology’s user-friendliness and utility predicts their attitude towards adopting digital tools. The study’s outcomes predominantly favour the facilitation of the process of learning. The effectiveness of a variety of technological tools including blogs, discussion forums, announcements and videos, which encourage engagement and enhance learning process overall, is highlighted by constructive feedback. Considering these findings, the study proposes that higher education institutions cultivate a professional migration identity by embracing platforms like Moodle. Platforms include zoom, video conferencing, TEAMS, and WhatsApp may be the first to undergo the transfer process. This strategic approach is recommended to effectively address technological hurdles, ultimately enhancing, and sustaining online teaching and learning practices.